IL-6 AND SERUM FERRITIN AS AN INDICATOR FOR GRADING SEVERITY AND EARLY MORTALITY IN INITIAL 72 HOURS OF ACUTE PANCREATITIS (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Acute pancreatitis is an acute inflammatory condition of the pancreas with a clinical spectrum ranging from mild self-limiting disease to severe pancreatitis associated with multiorgan dysfunction and mortality. Early prediction of disease severity is essential for appropriate management. Serum interleukin-6 (IL-6) and ferritin have emerged as potential early biomarkers of severity and prognosis. Objectives: To evaluate the role of serum IL-6 and serum ferritin as prognostic markers in acute pancreatitis and compare their predictive value with established scoring systems such as Ranson score and CT Severity Index (CTSI). Materials and Methods: This prospective observational analytical study was conducted in the Department of Surgery, Dr. D. Y. Patil Medical College Hospital and Research Institute, Kolhapur, over a period of two years. Patients aged 18–70 years presenting within 48 hours of onset of first-episode acute pancreatitis were included. Clinical assessment, laboratory investigations including serum amylase, lipase, IL-6, ferritin, LDH, ABG, and BUN, along with radiological evaluation by ultrasonography and contrast-enhanced CT, were performed. Ranson score and CTSI were calculated and correlated with disease severity. Results: Mild acute pancreatitis was the most common presentation. Increasing severity was significantly associated with higher Ranson scores, CT severity scores, LDH, serum lipase, IL-6, and ferritin levels (p